The Role Of Physical Activity On The Mental Health Of Physical Education Students: Systematic Literature Review - Silatul Rahmi (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Student mental health is an important concern, including for physical education students who are required to have a balance between physical and psychological. This study aims to systematically analyze the relationship between physical activity and mental health of physical education students based on the results of previous research. The method used is Systematic Literature Review (SLR) based on the PRISMA guidelines. Data was obtained from Google Scholar, ScienceDirect, ResearchGate, and SINTA with a publication period of 2018–2025. Of the 126 articles found, 12 met the criteria and were analyzed using CASP and JBI guidelines. The results of the study show that physical activity plays an important role in improving students' mental health, especially in reducing stress, improving psychological well-being, controlling emotions, and preventing depression. In addition, physical activity also supports the formation of character, confidence, and positive social relationships between students. These findings confirm that physical education not only focuses on learning motor skills, but also plays an important role in strengthening character and emotional balance. Thus, physical activity contributes greatly to the mental well-being of physical education students, so universities need to develop structured sports programs to support students' mental health.